PENGARUH SELF-EFFICACY, SOFT SKILL DAN HARD SKILL TERHADAP KESIAPAN KERJA MAHASISWA SEBAGAI GENERASI Z DI ERA REVOLUSI INDUSTRI 4.0 - Putri, Ananda Zania; Arini, Eti (UM. Bengkulu, 2025)
This study aims to determine the influence of self-efficacy, soft skills, and hard skills on the work readiness of Faculty of Economics and Business students, Class of 2022, at Universitas Muhammadiyah Bengkulu as Generation Z in the era of the Industrial Revolution 4.0. This research employs a descriptive quantitative approach, with the research subjects being FEB students from the 2022 cohort at Universitas Muhammadiyah Bengkulu. The study population consists of 288 students, and the sample size is determined using Slovin’s formula, resulting in 74 respondents. Data collection is conducted through questionnaires using an ordinal scale as the measurement tool. The data analysis techniques include multiple linear regression analysis and hypothesis testing. The research findings indicate that self-efficacy and soft skills have a positive but not significant influence on work readiness, while hard skills have a positive and significant influence on work readiness. The F-test (simultaneous test) results show that self-efficacy, soft skills, and hard skills collectively have a significant influence on the work readiness of Faculty of Economics and Business students, Class of 2022, at Universitas Muhammadiyah Bengkulu as Generation Z in the era of the Industrial Revolution 4.0.. Keywords: Self-efficacy, Soft Skills, Hard Skill, Work Readiness